Exploring The Influence of Work Commitment And Total Quality Management (TQM) on Teacher Performance: The Mediating Role of Self-Efficacy - Istiqomah, Alfina Damayanti; Pratiwi, Dian; Kholiq, Abdul (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This research explores the role of self- efficacy as a mediator in the influence between work commitment, Total Quality Management (TQM), and teacher performance. The survey method was used to collect data based on purposive sampling from 55 teachers from 3 junior high schools in Ponorogo Regency. Data collection was carried out using a questionnaire consisting of a Likert scale with 5 alternative answers. PLS-SEM analysis was used to analyze the data and test the model context. The results of the analysis show that work commitment has a significant effect on teacher self-efficacy and performance. Furthermore, self-efficacy was proven not to mediate the influence between work commitment and Total Quality Management on teacher performance. These findings highlight the importance of self-efficacy in facilitating the development of teacher performance through work commitment and the implementation of total quality management. The practical implication of this research is the importance of creating a work environment that supports the development of teacher self-efficacy. Educational institutions can provide social support, recognition of teacher contributions, and opportunities to participate in professional development activities. By creating a conducive environment to strengthen teacher self-efficacy, work commitment, and TQM implementation are hoped to run more effectively.